Repositioning teaching and teacher education in Nigeria (2004)
The art of teaching and the position of teachers in Nigeria today call for evaluation and immediate review. This is because teaching is a very important tool for all round development of every nation and teachers as the vehicle plays an important role in ensuring learners' success. The quality and availability of teachers have great implications on any educational system as the quality of education the learner receives depends largely on this. While teaching is an attempt to bring about desirable change in human learning, the teachers hold the trump cards to proper education and those entrusted to develop the head, heart and hands of others. In Nigeria today, pupils and teachers operate under very harsh conditions. The image of teaching is still very low even with the recent increase in salaries. Poor funding and facilities, incessant strikes, dearth of local and current books are few of the problems being faced. Repositioning teaching and teacher education in Nigeria will go a long way to provide solutions to these problems. Teachers and trainers should be fully involved in the on-going systematic innovative and qualitative reforms of education and emphasis should also be on organising and funding adequate training programmes for teachers. This paper examines the current positions of teaching and teacher education in Nigeria, highlighting the inadequacies in this area. Efforts have been made to offer suggestions on how teaching and teacher education could be repositioned in Nigeria.